2018
DOI: 10.1016/j.expneurol.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation-dependent remodeling of the corticospinal tract requires reactivation of growth-promoting developmental signaling pathways

Abstract: The corticospinal tract (CST) can become damaged after spinal cord injury or stroke, resulting in weakness or paralysis. Repair of the damaged CST is limited because mature CST axons fail to regenerate, which is partly because the intrinsic axon growth capacity is downregulated in maturity. Whereas CST axons sprout after injury, this is insufficient to recover lost functions. Chronic motor cortex (MCX) electrical stimulation is a neuromodulatory strategy to promote CST axon sprouting, leading to functional rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 86 publications
(150 reference statements)
1
31
0
Order By: Relevance
“…whereas, inhibiting Stat3 activation with AG490 reduced both bouton-like structures on corticospinal axons as well as levels of cFos expression in ipsilateral cervical spinal cord neurons without affecting corticospinal collateral formation (Zareen et al, 2018). These studies demonstrate that not only can electrical stimulation activate growth-promoting molecular pathways, it can strengthen the formation of novel connections needed to elicit functional recovery.…”
Section: Neuronal Activity and Molecular Control Over Axon Growthmentioning
confidence: 70%
See 2 more Smart Citations
“…whereas, inhibiting Stat3 activation with AG490 reduced both bouton-like structures on corticospinal axons as well as levels of cFos expression in ipsilateral cervical spinal cord neurons without affecting corticospinal collateral formation (Zareen et al, 2018). These studies demonstrate that not only can electrical stimulation activate growth-promoting molecular pathways, it can strengthen the formation of novel connections needed to elicit functional recovery.…”
Section: Neuronal Activity and Molecular Control Over Axon Growthmentioning
confidence: 70%
“…Chronic electrical stimulation of the motor cortex over ten consecutive days leads to activation of the mTOR pathway, inactivation of PTEN, and increased phosphorylation of ribosomal protein S6 ( Zareen et al, 2018 ). Additionally, this chronic stimulation drives increased levels of Janus kinase-signal transducer and activator of transcription (JAK/STAT) signaling ( Zareen et al, 2018 ), a critical mediator of cytokine signaling. Enhancing JAK/STAT signaling through deletion of suppressor of cytokine signaling 3 ( SOCS3 ) increases optic nerve regeneration ( Smith et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…mTOR is known to protect microtubules from microtubule stabilization 90 and to regulate the interaction of microtubules with CLIP170, a protein that associates with the tips of dynamic microtubules 91 , so it may be via these effects that neuronal activation alters microtubules. Moreover, previous studies showed that stimulation promotes corticospinal tract axonal sprouting and synapse formation via upregulation of mTOR and Jak/Stat signaling 92 and that inhibiting tubulin detyrosination to keep microtubules dynamic mimicked the axon growth-promoting effects of sustained GSK3 activity 51 , 93 . Collectively, these results support the view that various different pathways beneficial to nerve regeneration may converge on a common downstream effect, which is to shift the microtubule array of the axon, especially the distal axon, toward being less post-translationally modified and more dynamic.…”
Section: Discussionmentioning
confidence: 99%
“…The inconsistency may be due to the length of modeling time ( Nishijima et al, 2010 ; Mysoet et al, 2017 ). However, it has been reported that the activation of mTOR can promote axonal regeneration of corticospinal neurons, and then enhance neuronal activity ( Zareen et al, 2018 ). Our results suggest that rTMS may enhance the neuronal activity of the motor cortex through the activation of mTOR, leading to the improvement of gait disorders.…”
Section: Discussionmentioning
confidence: 99%